Matošev Emerson, ili konzekvencije flanerizma - Jukić, Tatjana (2014)
It was principally through Antun Gustav Matoš (1873-1914) that Croatian literature received its modernity for the twentieth century, as well as its sense of Europeanness. His essay on Emerson (1905) can be analyzed as part of the same agenda, especially in view of its marked Nietzschean overtones ; it is Nietzsche’s Emerson that Matoš brings to Croatian culture and, with it, a corresponding inflection of both Europe and philosophy. While this suggests that a Nietzschean America comes to shape the American phantasm for the twentieth-century Croatian modernity, I propose to discuss another operation which is equally critical to this placement of Emerson: the way in which Austrian-Hungarian cultural practices, definitive to Croatia at the time and at work in Matoš, decide Emerson’s profile and refract some of its Nietzschean features.
Projekt MZOS
HRV